What counts in teaching mathematics adding value to self and content - Schuck, Sandy; Pereira, Peter (Self study of teaching and teacher education practices, 2011)
In this book, internationally recognised scholars and practitioners synthesise current practice and research developments in the area of mathematics teacher education and mathematics education. The book?s two sections examine the role and significance of collaborations and critical friends in the self-study of mathematics teaching and teacher education; and the emerging conflicts, dilemmas and incongruities arising from the study of mathematics education practices. The book considers the insights gained from self-analysis regarding the practitioner themselves, as well as their pedagogical content, students and approaches. The contributions highlight the complexity, characteristics and features of mathematics education. The chapters reveal nuances in teaching and learning that are of particular relevance in mathematics education. In addition, the book contains ideas and suggestions on how to enhance the teaching of mathematical content to pre-service teachers. Accordingly, the book appeals to a wide audience of educators including education academics, teachers, student teachers and researchers. As teacher educators involved in mathematics education, reflection on practice and engagement in practitioner research is becoming increasingly important in our efforts to enhance our teaching. Teachers and student teachers also gain from the insights arising from such reflection. The knowledge and experience encapsulated in this book provides much for the mathematics education community to build on.